3D MXene microspheres with honeycomb architecture for tumor photothermal/photodynamic/chemo combination therapy. (15th February 2021) - Guo, Yaping; Wang, Hongshui; Feng, Xin; Zhao, Yunbo; Liang, Chunyong; Yang, Lei; Li, Mingjun; Zhang, Yongguang; Gao, Wei
Abstract: The MXene combining high surface area, prominent biocompatibility, and wide near infrared (NIR) absorption has been recognized as one of the most promising materials for tumor therapy. The application of MXene in tumor therapy is negatively affected by the current design methods lack the control of size distribution and the great tendency to agglomerate as well as poor photodynamic therapy. To solve the above problems, we report a facile strategy to process Ti3 C2 nanosheets into three-dimensional (3D) structure with honeycomb structure and anti-aggregation properties for synergistic therapy of chemotherapy, photothermal and photodynamic therapy. The 3D MXene is synthesized by spray drying, in which the MXene surface is oxidized to TiO2 . The microspheres present prominent NIR light trigger photothermal effect and excellent NIR light photostability, which respond in an on–off manner. Moreover, the microspheres exhibit outstanding drug-loading capability of doxorubicin (DOX) as high as 87.3%, and substantial singlet oxygen generation ( 1 O2 ) was shown under 808 nm laser and UV light irradiation. Our studies indicate that 3D MXene-DOX could effectively achieve Hela cells killing in vitro, which provides a multifunctional drug delivery platform as a prospective candidate for future combined cancer therapy.